Estrategias metodológicas y su incidencia en el aprendizaje significativo de los estudiantes en la modalidad aprendamos juntos en casa - Bermudez Segovia, Karen Isabel (2021)
This research thesis project focuses on the study of a complement between the appropriate strategies and techniques in meaningful learning seen from a pedagogical model, about the knowledge and interaction in the participation of children with their parents. An educational vision was made based on the relevant strategies for the investigative points that were, essential basic learning, educational plan, curricular pedagogical field among others. Each exposed topic will be socialized in detail, while limiting the source of information related to the case study, each step presented is related to the objectives set for the thesis project. A survey of 8 questions was applied to a certain population, around the educational community, recognizing the potential of the student as an individual and main actor within the work groups, achieving learning achievements with technological advances immersed in the integral development of the student. Thanks to the results obtained, the importance of the strategies implemented in each of the questions was analyzed from the point of view, graphs were established where the most significant results of the investigation can be observed. Thus it allowed to make conclusions that contributed to the analysis of the established hypotheses, this thesis is executed as a study that can provide a contribution to other studies immersed in this subject in the educational field; which allows to extend a wide study of the methodology.